The relationship between atlas hypoplasia and os odontoideum in children with Down syndrome: a preliminary case report. Issue 1 (January 2022) - Fujimoto, Yoh; Miyoshi, Kota; Oshima, Yasushi; Takikawa, Kazuharu; Takeshita, Yujiro; Nakamura, Takeomi; Tanaka, Sakae
Abstract : The purpose of this study was to evaluate the relationship of os odontoideum and the size of atlas among children with Down syndrome. Understanding the risk of developing myelopathy in asymptomatic cases is important in children with Down syndrome. Children with os odontoideum are considered to be at high risk of developing myelopathy because of instability; however, in cases that are complicated by atlas hypoplasia, the risk remains the same, regardless of instability. This retrospective case-control study assessed atlas hypoplasia in children with Down syndrome with or without os odontoideum. We retrospectively assessed the records of 59 patients (36 males and 23 females) with Down syndrome who underwent spinal X-ray evaluations at our hospital. The average age at examination was 5.0 years (range, 4–7). We evaluated the following radiologically: the presence of os odontoideum; atlas-dens interval; space available for the spinal cord at the atlas level (C1SAC); instability index; sagittal atlas diameter (SAD) as an index of atlas hypoplasia and C5 level SAC (C5SAC), adjusted for child growth. Os odontoideum was present in seven cases (12%). Between the groups with and without os odontoideum, there was no significant difference in age (mean, 5.2 vs. 5.0 years) or male/female ratio (57 vs. 62% males). The SAD/C5SAC (mean, 1.6 vs. 1.9) was significantly smaller in the group with os odontoideum than in those without os odontoideum. The instability index was not significantly different between the two groups. Children with Down syndrome and os odontoideum have small SAD. Evaluations for atlas hypoplasia are necessary.